Non-Formal Education and Popular Education. Documentary trace of two concepts to rethink the educational universe in the XXI century. - Eljure, Carlos; Ríos, Daniel (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The article is a literature review that studies 45 documents published between 2010 and 2021. It presents an approach to the conceptualization of Non-Formal Education and Popular Education in Latin America. The researches inquire about the tracing of concepts, historical construction in the continent and alternative practices. To develop the documentary review, a work plan was elaborated in which history, practices and their methodology and bibliographic search were categorized; the most transcendent contributions of each category were selected; finally, the analysis of the documents was carried out. It should be noted that Non-Formal Education and Popular Education are developed in similar contexts.